Wake losses optimization of offshore wind farms with moveable floating wind turbines. (1st January 2015) - Rodrigues, S.F.; Teixeira Pinto, R.; Soleimanzadeh, M.; Bosman, Peter A.N.; Bauer, P.
Highlights: We present a layout optimization framework for wind farms with moveable turbines. Using moveable wind turbines in optimized layouts maximizes energy production. Turbine and wind farm designers should cooperate to optimize offshore wind projects. Abstract: In the future, floating wind turbines could be used to harvest energy in deep offshore areas where higher wind mean speeds are observed. Currently, several floating turbine concepts are being designed and tested in small scale projects; in particular, one concept allows the turbine to move after installation. This article presents a novel layout optimization framework for wind farms composed of moveable floating turbines. The proposed framework uses an evolutionary optimization strategy in a nested configuration which simultaneously optimizes the anchoring locations and the wind turbine position within the mooring lines for each individual wind direction. The results show that maximum energy production is obtained when moveable wind turbines are deployed in an optimized layout. In conclusion, the framework represents a new design optimization tool for future offshore wind farms composed of moveable floating turbines.